2014
DOI: 10.2478/popore-2014-0022
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Swimming Males of Paratanaoidea (Tanaidacea)

Abstract: Abstract:In Tanaidacea morphological identification of male individuals to the species level is complicated by two factors: the presence of multiple male stages/instars confuse the assessment of sexual stage while strong sexual dimorphism within several families ob− scures the morphological affinities of undescribed males to described females. Males of Paratanaoidea are often morphologically quite different from females and have not been discovered for most genera so far, which has led to the assumption that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 32 publications
(49 reference statements)
1
32
0
7
Order By: Relevance
“…Partial COI sequences (651 bp, encoding 216 amino acids) were determined from the holotype specimen NSMT-Cr 25816 and the paratype specimen NSMT-Cr 25817; INSD accession numbers LC326400 and LC326401; the two sequences were identical. The sequence in the INSD most similar to our COI sequence, as determined by BLAST searches (Altschul et al 1990), was from the tanaidacean Typhlotanais variabilis Hansen, 1913 (Typhlotanaidae) (identity score 74%, query cover 70%, Błażewicz-Paszkowycz et al 2014). To date, no other anarthrurid nucleotide sequences have been deposited in public databases (DDBJ 2017).…”
Section: Methodsmentioning
confidence: 89%
“…Partial COI sequences (651 bp, encoding 216 amino acids) were determined from the holotype specimen NSMT-Cr 25816 and the paratype specimen NSMT-Cr 25817; INSD accession numbers LC326400 and LC326401; the two sequences were identical. The sequence in the INSD most similar to our COI sequence, as determined by BLAST searches (Altschul et al 1990), was from the tanaidacean Typhlotanais variabilis Hansen, 1913 (Typhlotanaidae) (identity score 74%, query cover 70%, Błażewicz-Paszkowycz et al 2014). To date, no other anarthrurid nucleotide sequences have been deposited in public databases (DDBJ 2017).…”
Section: Methodsmentioning
confidence: 89%
“…While the methods described in this article are specifically designed to work on deep−sea isopods, Asellota in particular, to some extent they provide a first step for molecular research on other peracarid groups as well. The methods for COI have been tested extensively and successfully on Amphipoda (Havermans et al 2013) and Tanaidacea (Błażewicz−Paszkowycz et al 2014). Most effort was spent on developing the protocols for the faster evolving DNA markers (COI, 16S, 12S) and especially the first two were most widely applied.…”
Section: Discussionmentioning
confidence: 99%
“…In the Ross Sea, before Błażewicz-Paszkowycz and Siciński (2014), only eight tanaid species were known: seven of these reported by Sieg (1983, 1986) ( Nototanais dimorphus (Beddard, 1886), Andrognathia plumosa Sieg, 1983, Pseuodoparatanais antarcticus Sieg, 1983, Typhlotanaoides insolitus Sieg, 1983, Akanthophoreus antarcticus (Vanhöffen, 1914), Typhlotanais greenwichensis Shiino, 1970, Cryptocopoides antarctica (Vanhöffen, 1914)) and one, Exspina typica (Vanhöffen, 1914) reported by Alvaro et al (2011). It is worthy to mention that the taxonomical status of Andrognathia plumosa has been recently questioned, as the species is only known from a male and it might represent the male of another species, namely Cryptocopoides antarctica (see Błażewicz-Paszkowycz et al 2014 for further details). Błażewicz-Paszkowycz and Siciński (2014), studying the materials collected with a Rauschert dredge (Rehm et al 2006), reported 40 species for the area, of which only 5 had been previously recorded in the area, 14 represented new species and the remaining species were new records for the area.…”
Section: Taxonomic Coveragementioning
confidence: 99%